In vivo effect of statins on the expression of the HIV co-receptors CCR5 and CXCR4 (2013)
ABSTARCT: During the HIV-1 replication cycle, several molecules including chemokine receptors and cholesterol are crucial, and are therefore potential targets for therapeutic intervention. Indeed statins, compounds that inhibit cellular synthesis of cholesterol and have anti-inflammatory and immunomodulatory properties were shown to inhibit HIV-1 infection by R5 tropic strains but not by X4 strains in vitro, mainly by altering the chemokine receptor/ligands axes. Therefore, the objective of this study was to characterize in vivo, the capacity of statins to modulate in HIV seronegative and chronically HIV-1-infected adults the expression of CCR5 and CXCR4, of their ligands and the tropism of circulating HIV-1 strains